Inventory Analysis For Perishable Item In Aircraft Manufacturing: A Study of PT.Dirgantara Indonesia - Wiranto, Efan; Adhiutama, Akbar (Journal of Business and Management, 2019)
PT Dirgantara Indonesia (Persero) is the first and only aircraft industry in Indonesia and the Southeast Asia Region. This company is owned by the Indonesia Government. PT Dirgantara Indonesia was established on April 26, 1976. PT Dirgantara Indonesia engaged in aerospace manufacturing, aerospace design development and being a sub-contractor for major aircraft industries in the world. During the production process, there is a delay in completion of aircraft, this is because of the time placing order and quantity order is not efficient yet. This study aims to solve the problem that focuses on inventory management of consumable and also a perishable item of sealant.These study analyses the root cause of the problem using the current reality tree, and the result is an ineffective inventory policy. Existing inventory model in the company isn’t effective and efficient yet, because there is a stock out for sealant and create a delay for 60 days and create opportunity lost Rp.26.247.376.680. After knowing the root cause, this study use EOQ and ROP with probabilistic demand and constant lead time to solve the problem and compare it with existing method in PT.Dirgantara indonesia. From the comparing calculation of existing and proposed method, the cost reduction is $ 55,044 or 23.2%.